Modification by SUMOylation Controls Both the Transcriptional Activity and the Stability of Delta-Lactoferrin - Escobar-Ramirez, Adelma (PLoS One, 2015)
Delta-lactoferrin is a transcription factor, the expression of which is downregulated or silenced in case of breast cancer. It possesses antitumoral activities and when it is re-introduced in mammary epithelial cancer cell lines, provokes antiproliferative effects. It is posttranslationally modified and our earlier investigations showed that the O-GlcNAcylation/phosphorylation interplay plays a major role in the regulation of both its stability and transcriptional activity. Here, we report the covalent modification of delta-lactoferrin with the small ubiquitin-like modifier SUMO-1. Mutational and reporter gene analyses identified five different lysine residues at K13, K308, K361, K379 and K391 as SUMO acceptor sites. The SUMOylation deficient M5S mutant displayed enhanced transactivation capacity on a delta-lactoferrin responsive promoter, suggesting that SUMO-1 negatively regulates the transactivation function of delta-lactoferrin. K13, K308 and K379 are the main SUMO sites and among them, K308, which is located in a SUMOylation consensus motif of the NDSM-like type, is a key SUMO site involved in repression of delta-lactoferrin transcriptional activity. K13 and K379 are both targeted by other posttranslational modifications. We demonstrated that K13 is the main acetylation site and that favoring acetylation at K13 reduced SUMOylation and increased delta-lactoferrin transcriptional activity. K379, which is either ubiquitinated or SUMOylated, is a pivotal site for the control of delta-lactoferrin stability. We showed that SUMOylation competes with ubiquitination and protects delta-lactoferrin from degradation by positively regulating its stability. Collectively, our results indicate that multi-SUMOylation occurs on delta-lactoferrin to repress its transcriptional activity. Reciprocal occupancy of K13 by either SUMO-1 or an acetyl group may contribute to the establishment of finely regulated mechanisms to control delta-lactoferrin transcriptional activity. Moreover, competition between SUMOylation and ubiquitination at K379 coordinately regulates the stability of delta-lactoferrin toward proteolysis. Therefore SUMOylation of delta-lactoferrin is a novel mechanism controlling both its activity and stability.